Aerodynamic and aeroacoustic behavior of span-wise wavy trailing edge modified SNL 100 m blade. Issue 1 (February 2019) - Yang, Seung Joon; Baeder, James D
The aerodynamic and aeroacoustic behaviors of wavy trailing edge modified flatback wind turbine blade have been investigated through numerical simulation. Previous studies have demonstrated aerodynamic and aeroacoustic benefits of the span-wise wavy trailing edge modification on the flatback trailing edge. The previous two-dimensional airfoil test cases have been extended to a complete set of design parametric study. Aerodynamic and aeroacoustic characteristics of the parametric study have been discussed, relying on the wave size, including recently added cases. Furthermore, in the current study, the wavy trailing edge modification has been applied to the Sandia flatback blade called "SNL100-03FB" and tested in rotating blade conditions. Several variations of the wavy trailing edge design have been tested for a range of wind speeds using an overset computation domain. The numerical simulation employs the in-house developed Navier–Stokes solver, OVERTURNS, as well as Graphics Processing Unit (GPU)-accelerated solver, GPURANS3D. Both are hybrid Reynolds Averaged Navier Stokes (RANS)/Large Eddy Simulation (LES) simulation; delayed detached eddy simulation has been used with the Spalart–Allmaras turbulent model and modifiedγ − R e θ − S A laminar–turbulent transition model.